Kedudukan Hukum Corporate Social Responsibility pada BUMD berdasar Undang-Undang RI Nomor 40 Tahun 2007 - Taufiq, Muuchamad (Jurnal Ilmu Manajemen Advantage, 2019)
This study aims to study, analyze, find the philosophical meaning of Corporate Social Responsibility (CSR). On the other hand this study aims to find out, explain the legal position of Corporate Social Responsibility in Regionally Owned Enterprises (BUMD). Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) has provided guidance that there is a corporate social responsibility to its environment. However, the UUPT does not contain clear sanctions so that its nature is not imperative and the target object is a company in the form of PT which is engaged in mining. Corporate Social Responsibility, which is defined as social and environmental responsibility, is a corporate obligation that is budgeted and counted as a company expense which is carried out with due regard to propriety and fairness. The research method used is the normative juridical approach. The object of the research is all the laws and regulations related to Corporate Social Responsibility and BUMD. Data collection techniques in this study, carried out by means of Library research. Furthermore, this research is expected to contribute to the development of the study of legal science, especially business law so that it can be a reference for similar research and further research.